Cardiogenic Shock Nursing Approach to Improve Patient’s Outcomes: A Scoping Review - Alrefaei, Salha Hamad; Hassan, Aisha Bishi; Assiri, Fatimah Fayaa (British Journal of Healthcare and Medical Research, 2022)
Background: Cardiogenic shock is undeniably a disorder that causes threats to life, and prompt resuscitation with revascularization of the coronary artery is the key to survival for patients with cardiogenic shock. Cardiogenic shock affects all organs of the body; therefore, this condition is best managed by the multidisciplinary teams of healthcare professionals, including the nursing professionals. Aim: This scoping review aims to analyze the approaches utilized by nurses to improve the clinical conditions of the patients diagnosed with cardiogenic shock. Methodology: This scoping review was carried out by synthesizing the evidence from previously published studies. 10 studies were used to analyze the approaches utilized by nurses to improve the clinical conditions of the patients diagnosed with cardiogenic shock. Results: Nurses have an essential role in providing holistic, comphensive care for patient with diagnosed with cardiogenic shock. Intergral nursing intervention has strongly improvement of patient outcome will be directed to restoration of organ perfusion, detecting clinical deterioration and provide psychological care to the patient. Conclusion: Maintaining mean arterial pressure is essential for end-organ perfusion. The key of nursing intervention are focus around provide oxygen therapy, appropriate fluids and therapy administration .Close patient monitoring and continous assessment play piovital role with cardiogenc shock patients because it provide evidence of effectiveness of treatment, detect and prevent deterioration of patient condition.